AT-13763 Kuppelfigur Athene am Kunsthistorischen Museum 8970 - Hubertl (Wikimedia Commons, 2015)
Notice iconographique issue de Wikimedia Commons. Titre: AT-13763 Kuppelfigur Athene am Kunsthistorischen Museum 8970.
Droits : Licence Creative Commons Attribution-Share Alike 4.0 via Wikimedia Commons
Keywords: œuvre d'art; tableau; sculpture; statue; wikimedia commons; Peintures